Literature in the foreign language classroom: a multidimensional role - Castro de Sasso, Diana; Reimel de Carrasquel, Sharon (Lenguas Modernas, 2017)
An examination of the ways in which the literary text has been used in foreign language programs during the last 15 years revealed that literature has been seen to play a series of separate and mutually exclusive roles, often at the expense of the student who is perceived as either a "foreign-language learner" or as a "reader of foreign literatu¡e". This paper attempts to show how literature should play but a single, multidimensional role in the foreign language teaching context, to describe how these dimensions are interconnected, as well as to demonstrate how the literary text, when seen from a holistic perspective, constitutes a resource for enhancing the personal and academic growth of the student.